Prevalence study on tobacco smoking and related factors of among residents of a suburb Kuala Terengganu, Malaysia - Myat Moe Thwe, Aung; Rahmah, Mohd Amin; Tengku Mohammad Ariff, Raja Hussin; Vidya, Bhagat (2019)
Introduction: The smoking is social malice causing ill health in smokers its prevalence commonly associated with social and demographic factors associated with smoking, specifically people’s knowledge and attitude towards smoking. Purpose of this study is to explore the factors associated with the prevalence of smoking among the respondents. Methods: This is a cross-sectional community study involving 349 eligible residents aged 15 years and above in Kampung Gong Penaga sub-urban village in Kuala Terengganu, Malaysia. Data were obtained via face-to-face interviews using a standardized, self-administered questionnaire. Multiple logistics regression with forwarding likelihood ratio method was applied to explore the factors associated with the prevalence of smoking among the respondents. Results: The overall prevalence of smoking was 27.2% (95% CI: 22.5, 31.9). The respondents’ knowledge score was ranged from 14 to 57 with mean score of 47.15 (6.89) meanwhile the attitude score was ranged from 50 to 133 with mean score of 102.13 (11.93) regarding tobacco smoking and its effect on health issues. Multiple logistic regression analysis revealed being male (p <0.001), being employed (p =0.025), having smokers in the family (p =0.002), having colleague or friend smokers (p <0.001) and total attitude score were found to be significant associated with prevalence of smoking among the respondents. Conclusions: The prevalence of smoking among Malaysians aged 15 years and over, remains high despite the implementation of several anti-smoking measures over the past decades. Tobacco smoking and its effect on health among Malaysian residents were directly influenced by overall attitude and their peers and their family smoking behaviours. Having knowledge does not appear to be related to smoking behaviours. Thus the study recommends health care providers, and authorities should program their preventive measures that focus on attitudinal change among smokers which promote anti-smoking activities and curb this social malaise.